Live-seminar: Managing droughts and floods for improved food security and livelihoods - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In a live-streamed science seminar broadcasted on Friday 4 October 2013, water expert Vladimir Smakhtin, from the International Water Management Institute (IWMI) talked about the issues and potential solutions to extreme water variability such as floods and droughts in Africa and Asia. This blog will give you a further introduction to the seminar topic: http://ow.ly/qxqnO Here you'll be able to find the presentation used during the live-streamed seminar: http://ow.ly/qxqru